Applying ecological concepts for mobile commerce : A case study for Celcom (Malaysia) Sdn Bhd / Arfah Jamian - Arfah, Jamian (2004)
The rapid growth in mobile data communications and the needs of business people exploring new channels and methods of supporting their customer bases and increase competitive market and add value to their customers has led to the emergence of Mobile Commerce (m-commerce). A study in Celcom (M) Berhad is perform, looking at the information environment factors put up by Celom to propel the success in mcommerce initiatives. The studies on ecosystem in mobile commerce using the idea specified by Davenport are appropriate to observe the factors prosper in wireless commerce today. The component inside the model will be discussed to see for interrelated aspect and issues in the area studies. Each viewpoint that comes from different background and is intended for different audience with various significance, but the basic concept of information ecology is a vision of recognizing the extricable relationships between people and technology. Adopting Davenport's Ecological model, this report shall discuss the finding of the study according to the 6 components of the information Ecology namely. Information Strategy, Information Architecture, Information Process, Information Staff, Information Politics, Information Culture and Behavioral